The political economy of the oil import quota - Barzel, Yoram; Hall, Christopher D. (Stanford, Calif. : Hoover Institution Press, Stanford University, 1977)
The book surveys the physical characteristics of the industry and the institutional arrangement which existed over the life of the quota (1959 - 1973).
Includes index.
Includes bibliographical references: p. 93-94.
occ 16/01/2019
Loans
Keywords: Petroleum industry and trade; Import quotas